CEO Gender, Massa Kritis Keberagamanan Gender Dewan, dan Kinerja ESG di Indonesia - Widijaya Widijaya; Eka Natiya Saputri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Objectives: This study examines how female CEOs, critical mass levels of female directors, and their interaction via gender homophily effect ESG performance among Indonesia firms Design/method/approach: A quantitative design employing multiple linear regression with a sample of 403 companies adhering to Global Reporting Initiative guidelines. Variables consist of female CEO, critical mass metric (WOMEN10, WOMEN20. WOMEN40) and interaction terms. Results/findings: Female CEOs have a beneficial and substantial impact on ESG performance. Results for critical mass show variability: WOMEN10 is significantly positive, WOMEN20 is significantly negative, and WOMEN40 shows no significance. Interaction effects are not significant, suggesting the gender homophily does not enhance board effectiveness in this case. Theoretical contribution: This research draws on Critical Mass Theory and the Upper Echelons perspective to enhance understanding of the role of female leadership in promoting sustainability.Practical contribution: Recommends that companies boost female representation in leadership positions to improve ESG outcomes. Limitations: Limited by variation in GRI disclosure quality across firms.